Protein–RNA and protein–protein interactions mediate association of human EST1A/SMG6 with telomerase - Redon, Sophie (Oxford University Press, 2007)
The human EST1A/SMG6 polypeptide physically interacts with the chromosome end replication enzyme telomerase. In an attempt to better understand hEST1A function, we have started to dissect the molecular interactions between hEST1A and telomerase. Here, we demonstrate that the interaction between hEST1A and telomerase is mediated by protein–RNA and protein–protein contacts. We identify a domain within hEST1A that binds the telomerase RNA moiety hTR while full-length hEST1A establishes in addition RNase-resistant and hTR-independent protein–protein contacts with the human telomerase reverse transcriptase polypeptide (TERT). Conversely, within hTERT, we identify a hEST1A interaction domain, which comprises hTR-binding activity and RNA-independent hEST1A-binding activity. Purified, recombinant hEST1A binds the telomerase RNA moiety (hTR) with high affinity (apparent overall K(d) = 25 nM) but low specificity. We propose that hEST1A assembles specifically with telomerase in the context of the hTR–hTERT ribonucleoprotein, through the high affinity of hEST1A for hTR and specific protein–protein contacts with hTERT.